2019
DOI: 10.1158/1541-7786.mcr-18-0173
|View full text |Cite
|
Sign up to set email alerts
|

A Leukocyte Infiltration Score Defined by a Gene Signature Predicts Melanoma Patient Prognosis

Abstract: Melanoma is the most aggressive type of skin cancer in the United States with an increasing incidence. Melanoma lesions often exhibit high immunogenicity, with infiltrating immune cells playing important roles in regression of tumors occurring spontaneously or caused by therapeutic treatment. Computational and experimental methods have been used to estimate the abundance of immune cells in tumors, but their applications are limited by the requirement of large gene sets or multiple antibodies. Although the prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…Next, we compared the level of transcriptome-based immune-related scores ( Table S5 ), namely, the Immune Score (calculated as previously reported in [ 31 ]) and the Leukocyte Infiltration Score (LIS; calculated as previously reported in [ 32 ]) in TRIM28 NORM and TRIM28 HIGH melanoma samples and observed significantly lower level of both scores in TRIM28 HIGH samples ( p < 0.0001; Figure 4 B,C). Furthermore, the GSEA confirmed significant depletion of the Immune Score-associated signature in the TRIM28 HIGH phenotype (NES = −3.210, p < 0.0001, FDR < 0.0001); ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Next, we compared the level of transcriptome-based immune-related scores ( Table S5 ), namely, the Immune Score (calculated as previously reported in [ 31 ]) and the Leukocyte Infiltration Score (LIS; calculated as previously reported in [ 32 ]) in TRIM28 NORM and TRIM28 HIGH melanoma samples and observed significantly lower level of both scores in TRIM28 HIGH samples ( p < 0.0001; Figure 4 B,C). Furthermore, the GSEA confirmed significant depletion of the Immune Score-associated signature in the TRIM28 HIGH phenotype (NES = −3.210, p < 0.0001, FDR < 0.0001); ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 83%
“…The Immune Scores were estimated based on the transcriptome profiles of each sample, as previously reported [ 31 ]. The Leukocyte Infiltration Scores (LIS) were calculated based on the expression level of 25 genes, as previously reported [ 32 ]. All immune-associated scores used in this study are shown in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the five-year survival of patients is low, and malignant melanoma will become a formidable disease once cancer cells colonize other tissues. 3,4 Immunotherapy with immune checkpoint inhibitors (inhibitory monoclonal antibodies against the cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed death 1 (PD-1/ PDL1) and targeted therapy (Vemurafenib and nivolumab) acted as a certain efficiency on metastatic melanoma; unfortunately, these immune-based therapies are not fully responsive in some advanced stage melanoma. 5,6 In this regard, it is desirable to adopt an efficient therapeutic strategy to overcome the shortage in successful treatment of metastatic melanoma based on immune checkpoint inhibitors and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies had attempted to develop prognostic models using different types of variables including clinicopathologic, mutation, mRNA, microRNA, and methylation variables. Zhao et al (6) identi ed a 25-gene signature that can effectively estimate the level of immune cell in ltration in melanoma, providing a robust biomarker signi cantly related to survival outcome (disease-speci c survival, post-recurrence survival, or overall survival). Multidimensional omics data were also utilized to provide more accurate prediction.…”
Section: Introductionmentioning
confidence: 99%